2016 12th International ACM SIGSOFT Conference on Quality of Software Architectures (QoSA) 2016
DOI: 10.1109/qosa.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Self-Learning Controllers for Elasticity Management in Dynamic Cloud Architectures

Abstract: Abstract-Cloud controllers support the operation and quality management of dynamic cloud architectures by automatically scaling the compute resources to meet performance guarantees and minimize resource costs. Existing cloud controllers often resort to scaling strategies that are codified as a set of architecture adaptation rules. However, for a cloud provider, deployed application architectures are black-boxes, making it difficult at design time to define optimal or pre-emptive adaptation rules. Thus, the bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 23 publications
(29 reference statements)
1
54
0
1
Order By: Relevance
“…Lastly, they are also criticized more often for their associated unwanted behaviour, termed as bumpy transition, that could lead the system to an oscillatory state [27,104,105]. On the other hand, knowledge-based control solutions utilizing machine learning [67,106,107] or neural networks [99,108] provide high levels of flexibility and adaptivity. However, such flexibility and adaptivity come at the cost of long training delays, poor scalability, slower convergence rate, and the impossibility of deriving stability proof [7,18,103,109].…”
Section: Discussion Issues and Challengesmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, they are also criticized more often for their associated unwanted behaviour, termed as bumpy transition, that could lead the system to an oscillatory state [27,104,105]. On the other hand, knowledge-based control solutions utilizing machine learning [67,106,107] or neural networks [99,108] provide high levels of flexibility and adaptivity. However, such flexibility and adaptivity come at the cost of long training delays, poor scalability, slower convergence rate, and the impossibility of deriving stability proof [7,18,103,109].…”
Section: Discussion Issues and Challengesmentioning
confidence: 99%
“…The authors of [47,67,97] proposed horizontal elasticity solution for Internet based systems using fuzzy systems. They all have used performance based metrics to make scaling decisions.…”
Section: Intelligentmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is shown that it is beneficial to use RL for classification of objects [18,21]. Reinforcement learning has also been used in many other applications, such as web applications [22,23], control and management problems [24,25], and also in grid and cloud computing [26,27].…”
Section: Introductionmentioning
confidence: 99%